Whose future is it anyway? Struggles for just energy futures - Krüger, Timmo; Eichenauer, Eva; Gailing, Ludger (Futures : the journal of policy, planning and futures studies, 2022)
This Special Issue addresses the challenges, claims, and contradictions in struggles for just energy futures. The eight articles share a critical position towards modernist assumptions and classical top-down approaches in the field of energy justice research. The authors draw on different empirical examples to discuss how energy futures are (and must be) the subject of conflict in societies. In analysing these conflicts, they focus on possible implementations of the just-transition concept, on the role of social movements and protest actors, and on the relevance of energy conflicts to the practice and theory of democracy. •The eight articles in this Special Issue share a critique of modernist assumptions.•It is not just about an energy transition, but about a civilisational transformation.•The sources of change lie outside the expert knowledge of a Eurocentric modernity.•Researching justice means questioning the epistemologies behind justice categories.